2022
DOI: 10.1002/brb3.2624
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlation between IL‐1β, IL‐12 and TNF‐γ, and cortisol levels in patients with panic disorder

Abstract: Introduction Chronic exposure to stress is a major risk factor in anxiety disorders (ADs) and can be accompanied by an altered microbiome–gut–brain axis and a compromised immune system. In recent years, the study of inflammatory processes in AD has gained special attention. Continued stress causes the reactivity of the hypothalamic–pituitary–adrenal (HPA) axis, the alteration of the intestinal microbiota and the consequent release of pro‐inflammatory cytokines, affecting the sensitivity to stress and the simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Quagliato and Nardi [ 123 ], in a systematic review, concluded that serum levels of the proinflammatory cytokines interleukin-6 (IL-6) and IL-1β were increased in PD patients. In a study on 41 PD patients (11 men and 30 women), in which levels of proinflammatory cytokines and cortisol were measured in saliva, it was found that levels of IL-1β, IL-12 and tumor necrosis factor-α (TNF-α) were negatively correlated with cortisol levels [ 124 ]; the authors concluded that in PD patients the inflammatory response related to the altered microbiome-gut-brain axis is associated with HPA axis reactivity and may influence the maintenance of anxiety. Although there is a paucity of information on the gut microbiota in PD, alterations in oral microbiota have been reported [ 125 ].…”
Section: Panic Disorder and Social Anxiety Disordermentioning
confidence: 99%
“…Quagliato and Nardi [ 123 ], in a systematic review, concluded that serum levels of the proinflammatory cytokines interleukin-6 (IL-6) and IL-1β were increased in PD patients. In a study on 41 PD patients (11 men and 30 women), in which levels of proinflammatory cytokines and cortisol were measured in saliva, it was found that levels of IL-1β, IL-12 and tumor necrosis factor-α (TNF-α) were negatively correlated with cortisol levels [ 124 ]; the authors concluded that in PD patients the inflammatory response related to the altered microbiome-gut-brain axis is associated with HPA axis reactivity and may influence the maintenance of anxiety. Although there is a paucity of information on the gut microbiota in PD, alterations in oral microbiota have been reported [ 125 ].…”
Section: Panic Disorder and Social Anxiety Disordermentioning
confidence: 99%